Association between Scabies Treatment and Parkinson's Disease: A Nationwide, Population-Based Study - Kao-Sung Tsai; Ming-Kuei Lu; Chao-Hong Liu; Fuu-Jen Tsai; Wen-Chi Chen; Huey-Yi Chen; Heng-Jun Lin; Cheng-Li Lin; Jen-Chih Lee; Kee-Ming Man; Chien-Yi Ho; Yung-Hsiang Chen (MDPI AG, 2024)
Background: Scabies is typically treated with scabicides like lindane, which poses a risk for acute neural toxicity. Lindane's prolonged use, particularly in agriculture, is linked to neurodegenerative diseases, including Parkinson's disease (PD), the second most common neurodegenerative disorder. This study aimed to evaluate whether scabies patients, particularly those treated with topical lindane, are at increased risk of developing PD. Methods: A nationwide population-based cohort study was conducted using data from Taiwan's National Health Research Institutes claims database from 2000 to 2018. The study included 27,173 patients with scabies, matched to a control group, with both groups followed for up to 18 years. The primary outcome was the incidence of newly diagnosed PD, and the hazard ratio (HR) for PD was calculated, focusing on those treated with topical lindane. Results: Among the 54,346 patients, 1639 (3.0%) were newly diagnosed with PD, with 993 (60.6%) from the scabies group and 646 (39.4%) from the control group. Scabies patients had an adjusted hazard ratio (aHR) of 1.46 (95% CI 1.32-1.63) for developing PD compared to controls. However, patients treated with topical lindane had a significantly lower aHR for PD at 0.15 (95% CI 0.12-0.19; p < 0.001), with a lower cumulative incidence of PD also observed in this group (p < 0.001). Conclusions: Scabies patients are at a 1.46-fold increased risk of developing PD, but those treated with lindane exhibit a significantly lower risk, suggesting potential protective effects of lindane against PD.